THE ROLE OF STRATEGIES IN DEVELOPING AND IMPROVING EDUCATIONAL PERFORMANCE IN UNIVERSITIES - Maher Ali Ahmed; SAAD SALIM GHANIM; Modher Ahmed khalf (Scholar Express Journals, 2022)
In fact, countries’ progress is measured according to the use of effective strategies, whether in education or otherwise; nevertheless, the underdevelopment countries lack modern strategies in higher education which is one of the pillars of the economic and social development plan in any society Alayoubi (2020). There are two important dimensions in this regard, namely, the economic efficiency and social justice, and the success achieving these dimensions is because of the performance management in higher education institutions in attempt to provide qualified graduates to the labor market, providing also, human resources and expertise this market needs, (Corti, L., & Gelati, C.,2020).
Keywords: the economic efficiency; social justice; the success achieving; strategies